2018
DOI: 10.1007/s00125-018-4561-y
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B1 infections are associated with the initiation of insulin-driven autoimmunity that progresses to type 1 diabetes

Abstract: CVB1 infections may contribute to the initiation of islet autoimmunity being particularly important in the insulin-driven autoimmune process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 41 publications
5
74
2
1
Order By: Relevance
“…Hence, one might conceive that the impact of viral infection could significantly vary between these 2 phenotypes with distinct immunogenetic characteristics. It was disclosed by DIPP study that the effect of CVB1 was restricted to islet autoimmunity starting with insulin autoantibody (IAA) and was not related to GAD‐driven autoimmune process . Diverging from the findings of the TEDDY study and the DIPP study, the positivity of enterovirus RNA in blood was not predictive of the later appearance of islet autoantibodies among a cohort of children from The Norwegian Environmental Triggers of Type 1 Diabetes (MIDIA) study .…”
Section: Environmental Determinantsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hence, one might conceive that the impact of viral infection could significantly vary between these 2 phenotypes with distinct immunogenetic characteristics. It was disclosed by DIPP study that the effect of CVB1 was restricted to islet autoimmunity starting with insulin autoantibody (IAA) and was not related to GAD‐driven autoimmune process . Diverging from the findings of the TEDDY study and the DIPP study, the positivity of enterovirus RNA in blood was not predictive of the later appearance of islet autoantibodies among a cohort of children from The Norwegian Environmental Triggers of Type 1 Diabetes (MIDIA) study .…”
Section: Environmental Determinantsmentioning
confidence: 95%
“…It was disclosed by DIPP study that the effect of CVB1 was restricted to islet autoimmunity starting with insulin autoantibody (IAA) and was not related to GADdriven autoimmune process. 68 suggested that surrounding microbes can start to train infants' immunity during pregnancy. 73 It is speculated that hygienic measures intended for prevention of infectious diseases via eliminating microbes from residents' living environment can accordingly disturb the native gut microbiome and remove microbial communities fundamental for training the immune system.…”
Section: The Role Of Viral Infections and Gut Microbiomementioning
confidence: 99%
“…Enteroviruses cause diverse diseases in humans with symptoms varying from mild, such as common cold, to more severe such as meningitis, encephalitis, and myocarditis [1][2][3][4]. In addition to acute diseases, enteroviruses have been associated with chronic diseases like type I diabetes or asthma [5][6][7]. However, there is no antiviral on the market against enteroviruses.…”
Section: Introductionmentioning
confidence: 99%
“…T he Enterovirus B species consists of tens of clinically relevant viruses, including over 30 serotypes of echoviruses and coxsackievirus B1 to B6 and A9. They can cause a wide variety of mild and severe infections, and many of them are also associated with the onset of type I diabetes and coeliac disease (1)(2)(3)(4). These viruses infect primarily gut epithelial cells and are naturally stabile in an acidic environment.…”
mentioning
confidence: 99%